Theories and Factors Followed for Setting Dividend Policy: Empirical Evidence from Pakistani Banks - Nasir Nadeem; Adnan Bashir; Sumaira Gulzar (UW Journal of Management Sciences, 2022)
Purpose: The main purpose of this study is to examine dividend theories and factors followed by banks in Pakistan for setting dividend policy from 2005 to 2015. Methodology/Design: Panel regression is used on annual data to check the impact of different factors on dividend policy of 24 Pakistani banks. Findings: The results of study reveal that banks in Pakistan follow the dividend smoothing hypothesis, life cycle theory, signaling theory and pecking order theory while setting dividend policies. The results also highlight that profitability; investment opportunities, last year dividend, growth and loan deposit ratio have significant influence on dividend policy of Pakistani banks. Implications: In the light of these results, it is recommended that management of banks needs to look into these factors while formulating dividend policy of their respective banks. By catering these factors they are in a position to set optimal dividend policy which not only fulfills banks’ growth and investment needs, but also satisfy investors’ need of return. Limitations: This study uses only listed commercial banks of Pakistan. All other i.e. specialized banks are excluded in this study.